A proteção social como pressuposto de atuação do Ministério Público do estado de Mato Grosso - Machado, Marcos Henrique (2013)
This paper analyzes the performance of the Public Ministry of Mato Grosso and its role in the effectiveness of the welfare state in Brazil, notably social protection proposed by CF/1988, focusing on its institutional functions, judicial and administrative, as well as the tools to garantiar the realization of social rights. It starts with the premise that the social function of the prosecutor is one of the topics of utmost importance for all to society; it is the sole recipient of the services provided by the institution. Relacina the principles normative constitutional and infra resulting from program guidelines, which ensure all citizens access to public social policies. Presents the legal system that puts the citizen with the right to demand the implementation of public policies that enforce health services, social security and welfare, through the prosecutor, who is responsible for the defense of individual rights unavailable, collective and diffuse, by constitutional mandate of the Brazilian state.